Electroejaculation: its technique, neurological implications and uses. - Brindley, G S (1981)
An improved technique for electroejaculation is described, with the results of applying it to 84 men with spinal injuries and five men with ejaculatory failure from other causes. Semen was obtained from most patients, but good semen from very few. Only one pregnancy has yet been achieved. The technique has diagnostic applications.